Estudos sobre o destino da arrecadação com as aplicações das medidas de defesa comercial - Oliveira, Thiago Vinicius Sayeg Egydio de (2009)
This thesis has as its main objective the clarification of the destination of revenues obtained by the Federal Government imposed as consequence of international trade disputes as well as the discussion on whether the delivery of any such revenues to the industries could be considered as an illegal subsidy by the other participants of the international trade regime